Volatile organic compounds in bile can distinguish pancreatic cancer from chronic pancreatitis: a prospective observational study - Navaneethan, Udayakumar; Spencer, Chad; Zhu, Xiang; Vargo, John J.; Grove, David; Dweik, Raed A. (Endoscopy, 2021)
Background Early and accurate diagnosis of pancreatic cancer is important. Our aim was to identify potential volatile organic compounds (VOCs) in the bile that can help distinguish pancreatic cancer from chronic pancreatitis. Methods In this prospective observational study, bile was aspirated from patients undergoing endoscopic retrograde cholangiopancreatography for chronic pancreatitis and pancreatic cancer, and the gaseous headspace was analyzed using mass spectrometry. Results The study included a discovery cohort of 57 patients (46 pancreatic cancer, 11 chronic pancreatitis) and a validation cohort of 31 patients (19 and 12, respectively). Using logistic regression analysis, the model [0.158 × age + 9.747 × log (ammonia) – 3.994 × log (acetonitrile) + 5.044 × log (trimethylamine) – 30.23] successfully identified patients with pancreatic cancer with a sensitivity of 93.5 % and specificity of 100 % (likelihood ratio 40.9, area under the curve 0.98, 95 % confidence interval 0.95 – 1.00). The diagnostic accuracy of this model was confirmed in the second independent validation cohort.Conclusion The measurement of VOCs in bile helped to accurately distinguish pancreatic cancer from chronic pancreatitis.